Lviv period for Smoluchowski: Science, teaching, and beyond - Rovenchak, A. (Condensed Matter Physics, 2012)
A major part of Marian Smoluchowski's achievements in science corresponds to the period of his work at the University of Lviv. Since this part is well described in the literature, in the paper the emphasis is made on some less known activities of this outstanding scientist: his teaching, his organizational efforts, and even his hobbies. The list of publications corresponding to the Lviv period is given.